Case Report: Hemodynamic consequences of severe supraventricular arrhythmia assessed by real-time magnetic resonance imaging in combination with electrocardiography - Röwer, Lena Maria; Tappel, Miriam Nathalie; Goundi, Mohamed Ali; Müller-Lutz, Anja; Abd El Rahman, Mohamed; Rieke, Jana; Steinhagen, Gerrit; Emmel, Mathias; Klee, Dirk; Pillekamp, Frank (Frontiers in Cardiovascular Medicine, 2025)
A 13-year-old asymptomatic boy presented with new-onset extrasystoles. His initial electrocardiogram (ECG) showed an irregular heart rhythm with some sinus beats but also numerous premature atrial contractions with aberrant ventricular conduction. While the initial cardiovascular magnetic resonance (CMR) study could be performed conventionally, more irregular extrasystoles impeded the follow-up study. Therefore, cardiac real-time MRI (RT-MRI) was performed in combination with a simultaneously acquired ECG, which enabled high image quality and the analysis of sinus and arrhythmic beats separately. RT-MRI volumetry of the sinus beat showed a stable systolic function in the left ventricle (LV) [LV ejection fraction of 54.3% and LV stroke volume of 61.1 ml/m2 (90th percentile)] and increased but stable LV volumes [LV end-diastolic volume of 112.6 ml/m2 (>97th percentile) and LV end-systolic volume of 51.1 ml/m2 (>97th percentile)]. In contrast, right ventricular (RV) function was reduced in sinus beats. In the premature contractions, RV and LV end-diastolic volume, stroke volume, and ejection fraction were lower, while the end-systolic volume was higher. In this patient with severe cardiac arrhythmias, conventional CMR could not provide adequate image quality. RT-MRI offered high image quality during free breathing and, in combination with an ECG, it provided a unique opportunity to analyze the hemodynamics of the premature beats and sinus beats as separate entities.